2004
DOI: 10.1055/s-2004-818945
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Quercetin Treatment on Vascular Function in Deoxycorticosterone Acetate-Salt Hypertensive Rats. Comparative Study with Verapamil

Abstract: This study analysed and compared the effects of chronic oral treatment with quercetin or verapamil on systolic blood pressure and vascular function in deoxycorticosterone acetate (DOCA)-salt hypertensive rats. Quercetin and verapamil inhibited the development of DOCA-salt-induced hypertension in a similar manner. DOCA-salt-hypertensive rats showed potassium depletion and oxidative stress, prevented only by concomitant quercetin administration. Quercetin and verapamil treatments reduced the endothelium-independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Quercetin, the most important dietary flavonol, present in multiple fruits and vegetables, reduces blood pressure in hypertensive animals and human after chronic consumption [9], [13], [31][37]. Herein, we show for the first time that the conjugated derivatives Q3GA and I3GA can exert antihypertensive effects when administered intravenously.…”
Section: Discussionmentioning
confidence: 76%
“…Quercetin, the most important dietary flavonol, present in multiple fruits and vegetables, reduces blood pressure in hypertensive animals and human after chronic consumption [9], [13], [31][37]. Herein, we show for the first time that the conjugated derivatives Q3GA and I3GA can exert antihypertensive effects when administered intravenously.…”
Section: Discussionmentioning
confidence: 76%
“…In this ex vivo study [ 39 ], they have demonstrated that quercetin (10 −5 M) acutely potentiates vascular relaxation induced by acetylcholine in 2K1C hypertensive rats, suggesting that quercetin shows its anti-hypertensive action by diminishing elastance of blood vessels. Galisteo et al [ 40 ] have reported the action of chronic oral intake of quercetin on systolic blood pressure and vascular function in deoxycorticosterone acetate (DOCA)-salt hypertensive rats. Quercetin enhances endothelial-dependent aortic dilatations in rats developed with DOCA-salt-induced hypertension in a similar manner to verapamil, a Ca 2+ channel blocker, which reduces blood pressure [ 40 ].…”
Section: Actions Of Quercetin On Blood Pressure In Human and Modelmentioning
confidence: 99%
“…Indeed, the effects of quercitin have been extensively investigated in animal models of CVDs, especially with regard to its antihypertensive effects. For example, a reduction of blood pressure after administration of quercitin in spontaneously hypertensive rats has been showed [ 188 ], as well as in salt-hypertensive [ 189 , 190 ] and NO deficient rats [ 191 ]. Recently, it has been reported that quercitin is able to ameliorate arterial erectile dysfunctions in rats via NOS regulation restoring, almost in part, the function of NO-cGMP pathway in the process of penis erection [ 192 ].…”
Section: Polyphenols and The No Signalingmentioning
confidence: 99%